Responsive geo-referenced content visualization based on a user interest model and level of detail - Seo, Daeil; Yoo, Byounghyun; Ko, Heedong (TAYLOR & FRANCIS LTD, 2015)
With steady growth in the deployment of sensor networks and widespread usage of mobile devices, the production of geo-referenced data is increasing exponentially, while analysis of the data typically uses a variety of application services on the Internet for activities such as logging and driving. This geo-referenced content needs to be classified and organized according to user interest for location-based decision-making. In this study, we define a user interest model and propose a method for organizing and presenting content based on the model. Our approach reconstructs geo-referenced content from a variety of sources based on points of interest organized by the user interest model. We present typical cases of using the proposed method, including a theme park resort, personal weather stations, and travel planning to show how the proposed method facilitates user decision-making based on the geo-referenced content.
Keywords: WEB